CHARACTERISTICS OF TURTLE NESTING HABITAT ON POPARENG BEACH, TATAPAAN DISTRICT, SOUTH MINAHASA REGENCY, BUNAKEN NATIONAL PARK AREA - Mukuan, Randi; Lawalata, Helen; Tengker, Anita; Setyawati, Iriani; Mege, Revolson Alexius (Universitas Negeri Manado, 2025)
Turtles They are among the world's protected animals and one of the rare, almost extinct species. The preservation of their habitat and knowledge of the traits of turtle-friendly habitats are two ways that the rescue and protection of these turtles must go on. For rescue operations, turtle sustainability, and sustainable coastal management, research is being conducted on the features of the turtle nesting habitats on Popareng Beach. This research aims to determine the characteristics of turtle nesting habitats and identify the parameters that hinder turtles from nesting at Popareng Beach, Tatapaan District, South Minahasa Regency. The method used in this research is the descriptive-exploratory method. With characteristic parameters consisting of beach width measurement, beach slope, sand temperature, sand humidity, sand texture, beach vegetation, and the presence of predators. From the research results, it shows that station 1 and station 2 have results that are suitable for turtle nesting habitats, with values obtained at station 1 being 88.33% and station 2 being 92%. Meanwhile, at station 3, with an evaluation score of 72%, it is considered fairly suitable and the station has tolerable limitations.